Edoxaban improves acute venous thromboembolism while preserving protein C and protein S levels. Issue 3 (March 2018) - Yamazaki, Hiromu; Yagi, Shusuke; Torii, Yuta; Amano, Rie; Oomichi, Yasuyuki; Sangawa, Teruaki; Fukuda, Daiju; Kadota, Muneyuki; Ise, Takayuki; Ueno, Rie; Hara, Tomoya; Kusunose, Kenya; et al.
Highlights: Edoxaban improves venous thromboembolism (VTE) and preserves protein C and protein S levels. Warfarin improves VTE and decreases protein C and protein S levels. Edoxaban may be preferable to warfarin for the inhibition of thrombin generation. Abstract: Background: It is well known that warfarin inhibits the synthesis of vitamin K-dependent anticoagulants, including thrombin, protein C and S, and factor Xa, leading, paradoxically, to an initial hypercoagulable state. Edoxaban, a direct inhibitor of activated factor X is widely used for the treatment of acute venous thromboembolism (VTE). However, the effect of edoxaban on circulating coagulation factors, in patients with acute VTE, remains unknown. Methods and results: We enrolled 57 patients with acute VTE with/without pulmonary embolism treated with edoxaban ( n  = 37) or warfarin ( n  = 20) in a clinical setting. Before treatment and 2 weeks after treatment, we evaluated thrombotic burden using ultrasound or computed tomography angiography. We also evaluated thrombin generation, represented by prothrombin fragment F1 + 2; thrombus degradation, represented by D-dimer; and levels of anticoagulants, including protein C, protein S, and antithrombin III. Both edoxaban and warfarin treatment improved thrombotic burden and decreased prothrombin fragment F1 + 2, and D-dimer. Edoxaban treatment preserved protein C and protein S levels. In contrast, warfarin decreased protein C and protein S levels. Neither treatment affected antithrombin III. Conclusions: Edoxaban improves VTE while preserving protein C and protein S levels, thereby indicating that edoxaban improves thrombotic burden while maintaining levels of anticoagulants.